Group size homophily data - Launay, J; Dunbar, R (University of Oxford, 2014)
These two csv files contain data analysed in Launay & unbar (in press) - 'Does implied community size predict likeability of a similar stranger?'. To be published in Evolution and Human Behavior. It is being made publicly available as part of the open access policy in European Research Council funded research, grant number 295663.